MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 2 SDN 031 SEBERANG KECAMATAN TEMBILAHAN MENGGUNAKAN MEDIA KOMIK - Ali Munawar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to improve the reading ability of grade 2 students at SDN 031 Across tembilahan sub-district of Indragiri Hilir, the subject of 11 students. The form of research is class action research to improve the learning process in class, the approach used is comic media to improve reading ability. The results showed that at the first meeting of cycle I teacher activity in learning activities only by 55% with a good enough category, then at the fourth meeting there was an increase of 90% with a good category. For student learning activities in the first cycle of meeting I obtained the percentage of student activity in the learning process only 53% with a good enough category, and at the fourth meeting obtained a percentage of 92% with a good category. The results of students' reading ability after learning reflection on the clarity indicator were scored by 3 in the moderate category, then on the word accuracy indicator was scored by 4 with a high category, and on the sound clarity indicator obtained a score of 4 with a high category. Judging from the results of the study of reading ability of grade 2 students at SDN 031 Seberang, there was a significant increase compared to the data in cycle I, it was proven that the application of comic media to students' reading ability is very effectively applied.